Epigenetic Modifier Supplementation Improves Mitochondrial Respiration and Growth Rates and Alters DNA Methylation of Bovine Embryonic Fibroblast Cells Cultured in Divergent Energy Supply - Crouse, Matthew S.; Caton, Joel S.; Claycombe-Larson, Kate J.; Diniz, Wellison J. S.; Lindholm-Perry, Amanda K.; Reynolds, Lawrence P.; Dahlen, Carl R.; Borowicz, Pawel P.; Ward, Alison K. (Frontiers in Genetics, 2022)
Epigenetic modifiers (EM: methionine, choline, folate, and vitamin B12) are important for early embryonic development due to their roles as methyl donors or cofactors in methylation reactions. Additionally, they are essential for the synthesis of nucleotides, polyamines, redox equivalents, and energy metabolites. Despite their importance, investigation into supplementation of EM in ruminants has been limited to one or two cofactors. Thus, we investigated the effects of supplementing four EM encompassing the methionine-folate cycle on bovine embryonic fibroblast growth, mitochondrial function, and DNA methylation. We hypothesized that EM supplemented to embryonic fibroblasts cultured in divergent glucose media would increase mitochondrial respiration, cell growth rate, and alter DNA methylation as reflected by changes in gene expression of enzymes involved in methylation reactions, thereby improving growth parameters beyond control treated cells. Bovine embryonic fibroblast cells were cultured in Eagle’s Minimum Essential Medium with 1 g/L glucose (Low) or 4.5 g/L glucose (High). Control medium contained no additional OCM, whereas treated media contained supplemented EM at 2.5, 5, and 10 times (2.5X, 5X, and 10X, respectively) the control media, except for methionine (limited to 2X). Therefore, the experimental design was a 2 (levels of glucose) × 4 (levels of EM) factorial arrangement of treatments. Cells were passaged three times in their respective treatment media before analysis for: growth rate, cell proliferation, mitochondrial respiration, transcript abundance of methionine-folate cycle enzymes, and DNA methylation by reduced-representation bisulfite sequencing. Total cell growth was greatest in High 10X and mitochondrial maximal respiration, and reserve capacity were greatest (P < 0.01) for High 2.5X and 10X compared with all other treatments. In Low cells, total growth rate, mitochondrial maximal respiration, and reserve capacity increased quadratically to 2.5 and 5X and decreased to Control levels at 10X. Biological processes identified due to differential methylation included positive regulation of: GTPase activity, molecular function, protein modification processes, phosphorylation, and metabolic processes. These data are interpreted to imply that EM increased growth rate and mitochondrial function beyond Control treated cells in both Low and High cells which may be due to changes in methylation of genes involved with growth and energy metabolism.